2022
DOI: 10.3390/antibiotics11050548
|View full text |Cite
|
Sign up to set email alerts
|

What Doesn’t Kill Them Makes Them Stronger: The Impact of the Resistance Patterns of Urinary Enterobacterales Isolates in Patients from a Tertiary Hospital in Eastern Europe

Abstract: (1) Background: The evolution of bacterial resistance to antibiotics is one of the factors that make infectious pathology an extremely dynamic field, also inducing a significant burden on public health systems; therefore, continuous updates on the bacterial resistance to antibiotics and their particular regional patterns is crucial for the adequate approach of various infectious diseases. (2) Methods: We retrospectively analyzed 354 patients with Enterobacterales urinary tract infections (UTIs), determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
1
4
1
Order By: Relevance
“…1A). Male gender has already been described as a likely risk factor in the occurrence of MDR UTIs [20]. In the previously cited study, the authors showed that female gender was a protective factor in the occurrence of antibioticresistant UTIs, which does not support the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…1A). Male gender has already been described as a likely risk factor in the occurrence of MDR UTIs [20]. In the previously cited study, the authors showed that female gender was a protective factor in the occurrence of antibioticresistant UTIs, which does not support the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Resistance phenotypes have been classi ed into seven categories: Multi-drug Resistant (MDR), Extensive Drug Resistant (XDR), Pandrug-resistant (PDR), Usual Drug Resistance (UDR), Di cult-to-Treat Resistance (DTR), Extended-spectrum cephalosporin-resistant (ESC), Carbapenem-resistant Enterobacterales (CRE). These different categories of resistance have been de ned in several previous studies [10,19,20].…”
Section: Classi Cation Of Antibiotic Resistance Phenotypesmentioning
confidence: 99%
“…Our results differ slightly from those of Miftode et al, who obtained MDR rates among E. coli , Klebsiella spp., and Proteus spp. of 60.3, 18.2, and 15.8%, respectively [ 23 ]. Our study detected half as many MDR E. coli strains (30%), but more MDR Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Related genes that have increasingly been found in clinical strains are, among others, bla KPC−2 , as well as bla NDM , and the presence of efflux pumps is also important [ 25 , 27 , 28 ]. Recent studies describing Enterobacter -induced UTIs indicate the involvement of extensive drug resistant (XDR), multidrug resistant (MDR), as well as carbapenem-resistant Enterobacterales (CRE) strains in the pathogenesis of infection in hospitalized patients in Eastern Europe [ 29 ].…”
Section: Introductionmentioning
confidence: 99%